Green Corridor Development as an Approach for Environmental Sustainability in Jordan - Al Masri, Abdelfattah; Özden, Özge; Kara, Can (European Journal of Sustainable Development, 2019)
The expansion of urban areas leads the loss of green spaces causing many environmental and economic problems. The infrastructure has been carried to the rural areas to deal with the needs of populations, reducing the green vegetation. This isolates one habitat area from other habitats and increases the fragmentation. A green corridor can connect fragmented habitats. Thus, this research aims to analyze and provide a green corridor in four different cities of Jordan. Through study some case studies, review of articles, researches, data collection, GIS, observations and maps derived from Jordanian ministries were used for the analysis of a green corridor in four cities in the northwest of Jordan. This research provides a comprehensive planning of the biogeographically areas, ecotourism sites and variety of vegetation in the protected areas of namely, Ajloun Forest Reserve and Dibben Forest Reserve, to link them in the biodiversity and conservation regions of the Al-Salt and north Amman, after identifying these diverse areas of vegetation cover and wildlife in each governorate. In addition, the research discusses ecological, environmental and economic effects of applying a green corridor as a sustainable city approach in Jordan. In other words, the purpose of this study is to suggest a sustainable proposal by analyzing green area zones and green corridor axes to improve the nature and the environment in Jordan. This proposal adapts urban areas with the establishment of green corridor connecting conservation areas in Jerash and Ajloun to Al-Salt and north of Amman. Such a green corridor can lead an increase of local and international tourism which may improve the economic strength and can increase the job opportunities for citizens to live in a more ecological urban environment. Keywords: Environmental sustainability; green corridor; connectivity; planning; Jordan